Analisis Faktor-Faktor Meal Experience dalam Menciptakan Perilaku Konsumen Pasca Pembelian di Jubilare Dine and Wine Bandung - Iskandar, Ridwan; Wardhana, Wishnu (Politeknik Pariwisata NHI Bandung, 2017)
Restaurant and cafe industry competition is getting tougher. Implementation of the strategy is not right, causing not guaranteed of loyal consumers. When loyalty is difficult to form, at least marketers should pay attention to post purchase consumer behaviour. Consumers relate to a product, there are important elements involved in this interaction process, namely the consumer experience. Therefore, marketers should be able to pack the elements that can be controlled by the marketer that can create a positive meal experience. The presence of the stimuli provided by the organizer restaurant / cafe to create a memorable meal experience in order to stimulate the post purchase behaviour of consumers, the formulation of the problem and the purpose of this study is: How meal experience gained consumers restaurant / cafe. How consumer behaviour and how the influence of post purchase experience meal consisting of food and drinks, atmosphere, cleanliness, service levels and prices obtained by the consumer in the creation of post purchase consumer behaviour. With 110 respondents, researchers used a non-random sampling technique that is accidental sampling in selecting samples and processed using computer software SPSS 17.00. Based on the results of the correlation matrix between the sub variables meal experience of the post purchase behaviour obtained correlation results sequentially, namely, food and beverages (0.77), atmosphere (0.68), hygiene (0.65), service level (0.72) and the price (0.75). Effect of meal experience of the post purchase behaviour has a very strong relationship, which with a correlation coefficient of 0.764, this shows that the meal experience. is able to make a positive contribution then post-purchase behaviour will tend to be positive anyway.